"It inspires me with rage and whips me / and there is no way out of it": The prison experience and the foundation of a new time in César Vallejo's Trilce (1922) - Quichua Ayvar, Grober Omar (2020)
This article analyzes the human condition and the proposal of a utopian future in César Vallejo's Trilce (1922). To do so, firstly, the logic that prevails within the prison world will be exposed: tedium, violence and impossibility of establishing affective bonds with each other. Secondly, in conjunction with the above, starting from the figure of the mother and 16 Grober Omar Quichua Ayvar (2020). "It inspires me with rage and it whips me / and there is no way out of it" the dispossessed, Vallejo's political commitment to materialize a fairer way of living together in a society where the capacity to love and the right to dissidence is rescued will be addressed.